2022
DOI: 10.1021/acs.chemmater.1c03722
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Shape Transformation of Eu3+-Containing Polymer Films through Modulating Dynamic Eu3+-Iminodiacetate Coordination

Abstract: Shape-transformative materials that can autonomously adopt three-dimensional (3D) shapes in response to environmental stimuli are of interest for the development of sensors and soft robotics. We herein report a new synthetic strategy to fabricate shape-transformable Eu3+-containing interpenetrating polymer films consisting of poly­(vinyl alcohol) (PVA) and poly­(3-iminodiacetate-2-hydroxypropylmethacrylate-co-acrylic acid) (P­(IDHPMA-co-AA)). Given the dynamic nature of Eu3+-iminodiacetate (IDA) coordination, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…This ability to prepare gradient Fe 3+ –catechol network structures also opens up the possibility of controlling the patterning of Fe 3+ –catechol domains in the X - and Y -directions. Soft lithography solution masking techniques coupled with controlled Fe 3+ diffusion allow 3D network films to be prepared with a diversity of hard (Fe 3+ –catechol) and soft (catechol only) network patterns. ,, To illustrate the utility of this strategy, swollen networks were covered with a PDMS mask that preferentially exposed distinct regions of the network surface to Fe 3+ via a reservoir of buffered Fe­(NO 3 ) 3 solution (Figure a). As iron diffusion is relatively slow in networks with high catechol grafting densities, this approach allows for control of feature sizes at resolutions of ∼700 μm (cf., QR code in Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This ability to prepare gradient Fe 3+ –catechol network structures also opens up the possibility of controlling the patterning of Fe 3+ –catechol domains in the X - and Y -directions. Soft lithography solution masking techniques coupled with controlled Fe 3+ diffusion allow 3D network films to be prepared with a diversity of hard (Fe 3+ –catechol) and soft (catechol only) network patterns. ,, To illustrate the utility of this strategy, swollen networks were covered with a PDMS mask that preferentially exposed distinct regions of the network surface to Fe 3+ via a reservoir of buffered Fe­(NO 3 ) 3 solution (Figure a). As iron diffusion is relatively slow in networks with high catechol grafting densities, this approach allows for control of feature sizes at resolutions of ∼700 μm (cf., QR code in Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Building on this success, there is significant opportunity for extending this design concept to a more modular synthetic strategy based on initial rapid and orthogonal free radical cross-linking followed by secondary functionalization with readily available catechol derivatives such as dopamine, alleviating the requirement for protection/deprotection of catechol moieties , (Figure ). The versatility of radical cross-linking systems and the wide availability of starting materials would also enable the preparation of patterned materials for soft robotics, , tissue engineering scaffolds, and high-strength, functional 3D printed materials …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of fluorescence quenching was competitive coordination of Cu 2+ and Eu 3+ to APA. [38,39] Once information www.advmattechnol.de was printed on the hydrogel by the ink, Cu 2+ diffused into the hydrogel and displaced Eu 3+ as the central ion coordinating with ligand APA. Since Cu-APA did not display fluorescence under 254 nm irradiation (Figure S7, Supporting Information), the fluorescence quenching of the patterned area was visible to naked eyes.…”
Section: Rewritable 2d Fluorescent Informationmentioning
confidence: 99%
“…25 Exploiting this dynamic Eu-iminodiacetate coordination, Yin et al reported a stimuli responsive shape transformation in polymer films consisting of polyvinyl alcohol (PVA) and poly (3-iminodiacetate-2-hydroxypropylmethacrylate- co -acrylic acid) (P-(IDHPMA- co -AA). 26 He and co-workers reported an Eu-DPA (dipicolylamine) containing random copolymer based film of poly( n -butyl acrylate- co -2-hydroxy-3-dipicolylamino methacrylate) (P( n BA- co -GMADPA)) which was responsive towards moisture. 27 Similarly, Holten-Andersen and co-workers proposed a strategy to obtain white light emitting hydrogels by tuning the concentration of carbon dots (for blue light emission), Eu 3+ and Tb 3+ ions in a polyacrylamide/polyacrylic acid gel network.…”
Section: Introductionmentioning
confidence: 99%